2014
DOI: 10.1080/00028487.2014.901248
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Juvenile Fish Condition and Survival to Adulthood in Steelhead

Abstract: Understanding how individual characteristics are associated with survival is important to programs aimed at recovering fish populations of conservation concern. To evaluate whether individual fish characteristics observed during the juvenile life stage were associated with the probability of returning as an adult, juvenile steelhead Oncorhynchus mykiss from two distinct population segments (DPSs; Snake River and upper Columbia River) were captured, photographed to determine external condition (body injuries, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…Evans et al. () found that juvenile length and condition were strong predictors of adult survival in steelhead from the Columbia and Snake rivers. In a study of Chinook Salmon from the Willamette River (a tributary of the Columbia River that enters downstream of the hydropower system) based on scale analysis, Claiborne et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evans et al. () found that juvenile length and condition were strong predictors of adult survival in steelhead from the Columbia and Snake rivers. In a study of Chinook Salmon from the Willamette River (a tributary of the Columbia River that enters downstream of the hydropower system) based on scale analysis, Claiborne et al.…”
Section: Discussionmentioning
confidence: 99%
“…Evans et al. () found that steelhead with general bodily injuries had higher susceptibility to avian predation but that the level of descaling was not influential. Gadomski et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Evans et al. ) and downstream life history decisions (Satterthwaite et al. ), which may influence their motivation to feed during late summer despite the increased effort required to acquire food in low‐drift and low‐flow conditions (Caldwell et al.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of Evans et al. () were used to capture, tag, and release steelhead smolts at Rock Island Dam (Figure ). Steelhead smolts were captured at the Rock Island Dam juvenile fish trap, anesthetized (with tricaine methanesulfonate), and PIT‐tagged (12‐ × 2‐mm tags [length × width]; 134.2 kHz) annually during 2008–2018.…”
Section: Methodsmentioning
confidence: 99%